PEMBELAJARAN KOMPUTER ANAK USIA DINI DI TAMAN KANAK-KANAK TELKOM PADANG - Pratiwi Asdani Mutia; Syahrul Ismet (Generasi Emas: Jurnal Pendidikan Islam Anak Usia Dini, 2019)
This study aims to describe computer learning for early childhood in Telkom Kindergarten Padang. The research uses descriptive method with a qualitative approach. The informants from this study were computer teachers. Data collection techniques in this study used observation techniques, interview techniques, and documentation techniques. Data analysis techniques used are data triangulation techniques. The result of children’s computer learning in the Telkom Kindergarten in Padang have been well implemented. Computer learning material given by teacher to children starts from easiest to the most difficult. In teaching computer material to children, the teacher uses several computer learning methods to make it easier for children to receive learning materials, namely cooperative methods, tutorial methods, demonstration methods, training methods and practice, and game methods. In its implementation, there are still obstacles faced by children’s, teachers, and computers used.